INTEGRATION OF CHARACTER VALUES IN THE RAIN PHENOMENON BY SCIENCE AND Al-QURAN - Novi Ayu Kristiana Dewi; Suhono Suhono; Marilin Kristian (AT-TAJDID, 2022)
One of the goals of Indonesian National Education is to develop the potential of students to become human beings who believe and are devoted to God Almighty. These goals can be formed through character education by inserting religious values in learning. One of them is in learning science which is integrated with the holy verses of the Koran. Science is a subject in school that discusses the phenomenon of rain. This research is a library research. The data collected in this study consisted of primary data obtained from the holy book of the Koran and secondary data in the form of data obtained from research articles. The data collected in this study were analyzed into information. The data in the study are in the form of verses from the Koran that discuss the phenomenon of rain which is studied for scientific evidence, so that the relationship between science and the Koran can be seen. Through this integration between science and the Koran, character values can be learned from the rain event. Based on the results of the study, it was found that rain is a hydrological cycle. Water on earth evaporates and rises to the atmosphere in the form of water vapor which then condenses at a certain height to form clouds. These clouds will move because of the wind so that they collect in one place and eventually condense into rain in the form of liquid, snow, or ice crystals which eventually fall back to earth. Rainwater that falls to the earth provides many benefits for the survival of humans, plants, and animals. The character values that can be learned from the rain event include acknowledging the oneness and majesty of God, being grateful for favors, and praying for goodness every time it rains to get blessings.